The effect of firm size, foreign ownership, and board diversity on carbon tax in companies listed on the Indonesia stock exchange - Gunawan, Patrizzia Placidia Aurel; Setijaningsih, Herlin Tundjung; Widuri, Rindang (Edelweiss Applied Science and Technology, 2025)
In response to increasing global concern over climate change, Indonesia is preparing to implement a carbon tax as part of its strategy to reach net-zero emissions by 2060. This study explores the influence of firm size, foreign ownership, government ownership, and board diversity on carbon tax liabilities among 23 energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Using 69 panel data observations, the study applies multiple linear regression models and employs Chow, Hausman, and Lagrange Multiplier tests to determine the most suitable model. The findings reveal that board diversity has a significant negative effect on carbon tax, indicating that companies with more diverse boards may engage in better environmental governance and cost efficiency strategies. In contrast, firm size and foreign ownership show no statistically significant relationship with carbon tax. These results emphasize the importance of board composition in shaping corporate responses to environmental regulation. Despite limitations related to sample size and data availability, the study contributes to the understanding of corporate environmental accountability in emerging markets and suggests implications for both policymakers and corporate leaders.